Circuit analysis I with MATLAB computing and Simulink/SimPowerSystems modeling - Karris, Steven T. (Orchard Publications, 2009)
An introductory text on electric circuit analysis with real-world examples and problem supplemented with MATLAB computations, and Simulink/SimPower models.